(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
Voodoo rites and the crime of enslavement: a new judicial recognition of the cultural variable (note to Criminal Court of Cass., sect. I, 3 February 2022, no. 3796) ABSTRACT: This contribution analyses the ways in which the Supreme Court dealt with a cultural element, that of the voodoo ritual, in a case of enslavement of some young Nigerian girls, forced into prostitution. Through a focus on the arguments that the judges of legitimacy use to attribute to this cultural variable a leading role in the compression of the personal freedom of the victims, it will be highlighted how the instrument of the anthropological expertise was important to bring out the network of meanings assumed by the ritual in the cultural perspective of the victims and to explicate its binding force. The attention given to the cultural context of the victims is interpreted here as symptomatic of an openness to cultural diversity, capable of providing effective protection and, for this very reason, a model that can also be replicated in other areas of the legal system, such as that of international protection. This point of view is explored through a brief analysis of some of the cultural contexts in which voodoo rituals are widespread and of their potential harm to constitutionally guaranteed rights, even outside of hypotheses strictly related to trafficking and prostitution. SOMMARIO. 1. I fatti all’origine della sentenza - 2. La trattazione dell’elemento culturale da parte dei giudici - 3. La complessità del fenomeno vudù - 4. Dal diritto penale alla protezione internazionale: vudù, stregoneria ed effettività della tutela dei diritti fondamentali.